Antibiotic Susceptibility Pattern of Some Clinical Gram Positive Isolates - Ehsan F. Hussein (Journal of Global Pharma Technology, 2017)
One hundred fifty samples have been collected through the period from July/2016 to December/2016. Were for isolation and identification of pathogenic gram positive bacteria. The samples were involved fifty samples from each skin, mouth and soil for isolate Staphylococcus aureus, Streptococcus pyogenes and Bacillus spp., respectively. Isolates were identified according to microscopic features and biochemical tests .Antibiotics susceptibility pattern were examined by disc diffusion method. The antibiotics explained different action modes and some of the have significant differences when comparisons together. The Trimethoprim antibiotic has high activity against Staph. aureus, and Strep. pyogenes while the Carbnicillin, Rifaxim in and Trimethoprim antibiotics have high activity against Bacillus spp.  These antibiotics were Amoxicillin, Ampicillin, Trimethoprim, Aztreonam, Phamethoxazole, Carbnicillin, Novobiocin, Erythromycin, Rifaximin, Penicillin-G, Oxolinic Acid, Bacitracin and Clindamycin. Trimethoprim antibiotic has high activity when comparison the activity of these antibiotics together.Keywords: Pathogenic bacteria, Trimethoprim, Antibiotics, Resistant.